Intervention Study to Improve Meal Habit, Sleep Habit, Circadian Typology And School Marks in Japanese Elementary School Students - Takeuchi, Hitomi; Nakao, Mizuka; Kurose, Wataru; Kawada, Takahiro; Noji, Teruki; Nakade, Miyo; Tsuji, Fujiko; Krejci, Mirada; Harada, Tetsuo (Journal of Sleep And Sleep Disorder Research, 2017)
Purpose: An intervention program was performed to improve meal habit, sleep habit and academic marks at school. This program was called “Super Meal Educational Program” which was supported by Japanese Ministry of Arts, Sports, Sciences and Education. Effects of the intervention were evaluated by comparing an integrated questionnaire study held both before and after the intervention of a half year. Method: The intervention program consisted of a lecture on sleep health and diurnal rhythms on children by an university professor, a series of lectures and practical classes by elementary school teachers on foods which can be collected nearby, and also practical courses as excursions to learn traditional meals and several foods resources which are products nearby. Integrated questionnaire study and also government official academic achievement test were performed before and after the intervention for 6 months in May to November, 2015. An integrated questionnaire was administrated to elementary school students of grades 1 to 6 (7-12 years old). For the younger students aged 6-9 years old, parents (mostly mothers) answered the questionnaire instead of their children. The participants consisted of 40 to 55 students in each grade from the first to the six one of the elementary school. The rate of answer to the questionnaire was more than 95% and the number of data used for statistic analysis was 295 before and 286 after the intervention. The integrated questionnaire included questions on the diurnal type scale (DTS), sleep habits, meal habits, and other questions on their environments and life-habits. Result: In the histogram on distribution of the diurnal type scale scores (DTS) before intervention, the students which occupied 25% evening-typed significantly shifted to more morning-typed ones after the intervention (p<0.001). There was significantly negative correlation between DTS scores before intervention and the amount of increased change in DTS during the intervention period (r=-390, r<0.001). For all students in the elementary school, there were no significant changes in sleep quality, bedtime in weekdays, wake up time and sleep hours before and after the intervention period. There was negative correlation between sleep hours in weekday before intervention and increased amount in sleep hours before and after that (r=-0.545, p<0.001). The longer the sleep hours were shifted longer during intervention, the better the academic achievement mark of mathematics was after the intervention (students in the second, third and fifth grades: p=0.001). Conclusion: At least for the students who had been originally evening-typed, the intervention on meal habits may be effective for longer sleep hours and improved school achievement and marking for especially mathematics in elementary schools.
Keywords: Academic Achievement; Sleep Habits; Circadian Typology; Meal Habits; Elementary School Students; School Intervention